False selection of syringe-brand compatibility and the method of correction during target-controlled infusion of propofol - Yun-Jeong Chae (Korean Journal of Anesthesiology, 2013)
BackgroundWe evaluated volumetric differences of syringe brand compatibilities, and investigated the impact of false brand settings on target-controlled infusion (TCI) and their methods of correction.MethodsGravimetric measurement of 10 ml bolus infusions was performed using BD Plastipak (BDP) and Terumo compatible syringes, while setting to 7 different kinds of brand compatibilities (BDP, Sherwood Monoject, BD Perfusion, Braun Perfusor, Braun Omnifix, Fresenius Injectomat, and Terumo). To investigate the performance of TCI using BDP with a false setting to Terumo (BDPTERUMO) and Terumo to BDP (TERUMOBDP), 24 TCI targeting 4.0 µg/ml of effect-site concentration (Ceff) of propofol were performed. Subsequently, another 24 TCI were evaluated for simple corrections of false settings at 30 min. We also investigated 24 TCI using active corrections (fill-up for BDPTERUMO, evacuation for TERUMOBDP) based on the pharmacokinetics of propofol. The Ceff at 30 min of TCI and time to normalize to ± 5% of target concentration (T±5%target) were compared.ResultsThe Ceff of BDPTERUMO showed negative bias and 17.2% inaccuracy, and the Ceff of TERUMOBDP showed positive bias and 19.5% inaccuracy. The Ceff at 30 min showed no difference between the methods of correction in BDPTERUMO or TERUMOBDP. The T±5%target in both the active corrections was significantly shorter than that of each simple corrections (P < 0.001).ConclusionsFalse brand setting of syringe proportionally maintained different predicted concentrations as much as the volumetric differences of syringe brand. Based on the results, it is proposed that correction methods based on pharmacokinetics could effectively normalize the differences, without giving up the wrong TCI.